Quantitative rescattering theory of correlated two-electron momentum spectra for strong-field nonsequential double ionization of helium - Chen, Zhangjin; Liang, Yaqiu; Lin, C. D. (My University, 2010)
We study the correlated two-electron momentum spectra of the nonsequential double ionization (NSDI) of an atom in an intense laser field based on the recently developed quantitative rescattering (QRS) theory. According to the rescattering model, an electron that was released earlier in the laser pulse may return to collide again with the target ion. NSDI can occur directly if this electron knocks out another electron in a process similar to the (e,2e) process or indirectly by first exciting the target ion to an excited state which is later ionized by the laser field. Using QRS, we obtain the returning electron wave packet. By multiplying this wave packet with standard field-free (e,2e) differential cross sections, or with inelastic electron-impact excitation cross sections and the subsequent tunneling ionization, we obtain the correlated two-electron momentum spectra. The calculated spectra agree mostly with the experimental data. However, experimental data show additional features that cannot be accounted for by these two mechanisms only, and other mechanisms for NSDI are suggested. The contributions of these mechanisms to the longitudinal ion momentum distributions are also analyzed. The present quantum mechanical QRS calculation verifies the validity of rescattering model for the NSDI processes at the most fundamental and detailed level.